HOW DOES THE TRANSITION FROM HIGH SCHOOL TO COLLEGE IMPACT STUDENTS’ ACADEMIC PERFORMANCE AND MENTAL HEALTH? (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article will address the transition from school to college as an important period in the life of a student with respect to its effect on their mental health and academic performance. This study covers the issues faced by students as well as the learning load and social adaptation affecting their well-being. Qualitative research techniques were adopted for this task, and interviews with students of Kimyo International University in Tashkent (Samarkand Branch) were conducted. Also included in this article are all the results of interviews. The study focuses on university education, overcoming obstacles and family support as the most significant predictors of successful transition. The way forward is improving school preparation programs, providing psychological and academic guidance in universities, and teaching students stress management. Overcoming such obstacles will help students perform well academically and enjoy psycho-emotional stability.